Exploring the profile and risk factors associated with self-harm ideation and behaviors in adolescents with high psychoticism - Xu, Xiao-Ming; Jiang, Ru-Hong; Han, Yu-Shuang; Wang, Wo; Ai, Ming; Chen, Jian-Mei; Cao, Jun; Chen, Xiao-Rong; Lv, Zhen; Xu, He-Yan; Ding, Da-Qin; Hong, Su; et al. (Frontiers in Psychiatry, 2025)
BackgroundAs a core personality trait closely linked to mental health outcomes, psychoticism warrants particular attention in adolescent populations. The association between elevated psychoticism levels and self-harm ideation and behaviors (SIB) remained insufficiently characterized, especially regarding specific risk profiles. This study aims to delineate SIB characteristics and identify risk factors among adolescents with high psychoticisme.MethodsIn this large scale cross-sectional study, 6,027 adolescents aged 16-18 years scoring ≥70th percentile on the psychoticism dimension (Revised Short Form of the Eysenck Personality Questionnaire, EPQ-RSC) were recruited from 63 schools. Data on demographic characteristics and SIB patterns were collected via standardized electronic questionnaires through a secure online platform. Binary logistic regression analyses with adjusted odds ratios (aOR) identified significant SIB predictors.ResultsAdolescents with high psychoticism demonstrated striking SIB prevalence patterns: 62.8% reported life meaninglessness, 47.2% expressed death wishes, and 34.7% acknowledged suicidal/NSSI ideation within the past year, with 27% specifically endorsing such ideation within the past month. Actual self-harm rates were 4.7% (lifetime), 1.64% (past year), and 0.37% (past month). Predominant triggers included family conflicts (32.9%), while primary motives centered on pain alleviation (51%). SIB incidence showed significant dose-response relationship with psychoticism severity (p<0.05). Rural residency (aOR=1.32, 95% CI 1.04-1.675) and typical high psychoticism (aOR=1.509, 95% CI 1.16-1.963) emerged as key risk factors. Increasing age conferred significant protection against self-harm ideation (aOR=0.687, 95% CI 0.627-0.753), whereas female sex demonstrated differential risk modulation patterns across SIB (lifetime self-harm behavior aOR=2.053 vs. past-month self-harm ideation aOR=0.648).ConclusionOur findings highlight the critical need for targeted interventions addressing modifiable determinants. Prioritizing female adolescents and those with higher psychoticism traits is recommended, supported by evidence-based family psychoeducation programs and enhanced accessibility of community mental health services with specific focus on emotion regulation training.